Tests and design method on overall buckling behaviours of welded I-section two-span continuous beams for Q460 high strength steel. (15th February 2022) - Zhao, Jinyou; Ding, Wensheng
Highlights: Tests on welded I-section two-span continuous beams for Q460 high strength steel. The finite element model considering initial geometric imperfections and residual stresses was developed and verified against tests. The extensive finite element parametric analyses were carried out for study on design method. The overall buckling design method of two-span continuous beams for Q460 high strength steel in the relevant code was assessed and the corresponding suggestions were proposed. Abstract: To investigate the overall buckling behaviours of welded I-section two-span continuous beams for Q460 high strength steel and assess the reliability of the overall buckling design method for such beams stipulated in the Standard for design of high strength steel structures (JGJ/T483-2020) of China, a total of six two-span continuous beams were tested under concentrated loads, and the overall buckling modes and capacities were obtained. The finite element model (FEM) considering initial geometric imperfections and residual stresses was established and validated through comparing with the test results, and extensive parametric analyses were carried out through the validated FEM. Based on the formula of the elastic critical moment for simply supported beam given in Standard for design of steel structures (GB50017-2017) and the finite element analysis (FEA) results, the formula of the elastic critical moment for two-span continuous beam was proposed. The above proposed formula was substituted into the buckling factor formula in JGJ/T483-2020 to obtain the overall buckling design curves of two-span continuous beams for Q460 high strength steel. Furthermore, the obtained design curves were compared with the test and FEA results, which indicates that the design method in JGJ/T483-2020 is suitable for the overall buckling design of two-span continuous beam for Q460 high strength steel with non-dimensional slenderness value less than 1.5, and the design method in JGJ/T483-2020 is relatively conservative for the overall buckling design of two-span continuous beam for Q460 high strength steel with non-dimensional slenderness value greater than 1.5.